Interferon-α increases monocyte migration via platelet–monocyte interaction in murine intestinal microvessels - Higashiyama, M (Blackwell Science Inc, 2010)
The aim of this study was to investigate the effect of interferon (IFN)-α on recruitment of platelets and monocytes within the murine small intestinal venular endothelium. Monocytes were isolated from bone marrow of C57B6 mice. Platelets were collected from murine blood. Rolling and adhesion to submucosal microvessels in the small intestine were examined under an intravital fluorescence microscope after injection of fluorescein-labelled monocytes or platelets. In some mice, IFN-α (5 × 10(5)U/kg) was administered intraperitoneally. After treatment with an antibody against P-selectin, changes in monocyte and platelet migration were also investigated. Changes in monocyte migration under the condition of thrombocytopenia were also investigated. Platelets and monocytes interacted with murine intestinal microvessels, although only few platelets and monocytes showed migration behaviour. Intraperitoneal injection of IFN-α enhanced the migration of both platelets and monocytes in the intestinal microvessels. Pretreatment with anti-P-selectin attenuated the increase in migration of platelets and monocytes induced by administration of IFN-α. Thrombocytopenia decreased the rolling ratio of monocytes, suggesting that the effect of IFN-α on migration was P-selectin-dependent, derived from both the endothelium of microvessels and platelets. The results of this study suggest that IFN-α acts as a potent proinflammatory agent via its stimulatory effect on the endothelium–platelet–monocyte interaction in intestinal microvessels by a P-selectin-dependent mechanism.